Pendidikan Keteladanan Wanita Shalihah Dalam Kitab Mir’ah Al-Mar’ah Karya Abu Muhammad Zaini Annur Hidayatullah Ibn Alhaj Luqman Al-Hakim AlAlabi - Sari Wati; Rusdi Rusdi; Andi Murniati (Instructional Development Journal, 2021)
bnm